Evaluación de eugenol (extracto del clavo de olor) como limpiador bucal natural en caninos en la Clinica Veterinaria Patitas Traviesas en la parroquia de Machachi cantón Mejía - Azogue Pilicita, Dario Alexander (2015)
This research was realized in the Pichincha Province, Mejia Canton in the "Patitas Traviesas" Veterinary Clinic” that lasted fifteen days, the objective was the evaluate eugenol as a natural oral cleanser in canine the study consists of three treatment using the compound eugenol 1%, 2% as compared to natural mouth cleaners a compound commercial use Aquadent (xilitol), in order to decrease the percentage of colony forming units (UFC) in canines mouth cleaning is performed every 48 hours in the three treatments and decreased bacterial loads in hisopados were evaluated in the oral mucosa (CFU / ml) In the first sample was obtained for first treatment averaged with Eugenol 1% 1,368,000 colony forming units (UFC), for second treatment Eugenol 2% 2,768,000 (UFC) vs. third treatment Aquadent (Xilitol) 756,000 was obtained (UFC) then the five washed and finally results for first treatment with an average 1% Eugenol 45500 colony forming units (UFC), for second treatment 2% Eugenol 100200 (UFC) vs. third treatment Aquadent (Xilitol) 11936 was obtained (UFC)....